2023
DOI: 10.1038/s41420-023-01387-0
|View full text |Cite|
|
Sign up to set email alerts
|

Autophagy in hepatic ischemia–reperfusion injury

Abstract: Hepatic ischemia–reperfusion injury (HIRI) is a major complication of liver resection or liver transplantation that can seriously affect patient’s prognosis. There is currently no definitive and effective treatment strategy for HIRI. Autophagy is an intracellular self-digestion pathway initiated to remove damaged organelles and proteins, which maintains cell survival, differentiation, and homeostasis. Recent studies have shown that autophagy is involved in the regulation of HIRI. Numerous drugs and treatments … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 146 publications
(169 reference statements)
2
14
0
Order By: Relevance
“…Studies have demonstrated that SSRIs can inhibit liver tumor formation induced by β-catenin mutation in zebrafish [ 96 ]. Autophagy is an intracellular mechanism that allows cells to self-digest damaged organelles and proteins, thereby maintaining cell survival, differentiation, and overall homeostasis [ 97 ]. While autophagy generally plays a protective role in cells, excessive autophagy can result in cellular damage.…”
Section: -Ht In Hccmentioning
confidence: 99%
“…Studies have demonstrated that SSRIs can inhibit liver tumor formation induced by β-catenin mutation in zebrafish [ 96 ]. Autophagy is an intracellular mechanism that allows cells to self-digest damaged organelles and proteins, thereby maintaining cell survival, differentiation, and overall homeostasis [ 97 ]. While autophagy generally plays a protective role in cells, excessive autophagy can result in cellular damage.…”
Section: -Ht In Hccmentioning
confidence: 99%
“…Bone marrow, adipose tissue, and umbilical cord MSC-EVs inhibit cardiomyocyte apoptosis and promote angiogenesis, thus improving cardiac function and protecting myocardium [ 308 ]. The mechanism by which natural umbilical cord MSC-EVs alleviate liver injury after ischemia/reperfusion is due to the binding of miR-20a and two upregulated genes, Beclin-1 and FAS 3′ UTRs, thereby inhibiting apoptosis [ 309 ]. Injecting MSC-EVs locally into a murine model of retinal detachment (RD) significantly reduces levels of inflammatory cytokines TNF-α and IL-1β, Atg5 cleavage, and apoptosis of photoreceptor cells, thereby preserving the normal structure of the retina [ 310 ].…”
Section: Pharmacology Of Extracellular Vesiclesmentioning
confidence: 99%
“…Recent studies have indicated that autophagy is involved in IRI regulation. Direct regulation of autophagy alleviates IRI following transplantation ( 104 ). Ferritinophagy is a type of autophagy that targets ferritin to maintain balanced intracellular iron levels.…”
Section: Crosstalk Between Cgas–sting Pathway and Irimentioning
confidence: 99%